2020
DOI: 10.1097/mej.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of two-thumb versus two-finger chest compression for cardiopulmonary resuscitation in an infant manikin model

Abstract: Objective The loading force applied in infant external chest compression (ECC) has not been determined. The objective of this crossover study was to quantify the actual force involved in two-thumb (TT)-encircling hands and two-finger (TF) methods during infant cardiopulmonary resuscitation. Methods A total of 42 emergency medical professionals performed lone rescuer infant external chest compression (ECC) with TF and TT methods. The order of two methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…Finally, the TF technique has high compression pressure only at the fingertips, which may easily be misplaced with fatigued rescuers. In the Tsou et al study [25], the mean compression force of the TT technique was significantly higher than that of the TF technique, and the decrease of compression-force delivery during CPR was also significant in the TF technique. With respect to ergonomics, the TT technique is much superior to the TF technique.…”
Section: Discussionmentioning
confidence: 83%
“…However, we additionally evaluated complete chest recoil that is a crucial component known to contribute to HQ-CPR [39]. Second, one more eligible study was identified and included in the present study [25]. Third, we adopted a GOSH plot and unsupervised-learning algorithms to aid in exploring potential outliers contributing to the substantial heterogeneity observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies were crossover RCTs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], whereas three were parallel RCTs [ 28 , 29 , 30 ]. In Haque et al’s study [ 30 ], a total of 80 participants were randomly allocated to five groups, namely the infant TF, infant TT, child one-hand, child two-hand, and adolescent two-hand groups, with 16 participants in each group.…”
Section: Resultsmentioning
confidence: 99%
“…First, leave-one-out analysis revealed that all the pooled estimates after omitting one study at a time still lie within the 95% confidence interval of the overall estimate ( Figure 16 A). Second, the Baujat plot showed two studies located at the right side of the plot [ 18 , 21 ] ( Figure 16 B). The corresponding subsets including these potential outliers were shown in Figure 16 D. However, the GOSH plot remained heterogeneous after excluding the potential outliers ( Figure 16 C).…”
Section: Resultsmentioning
confidence: 99%